The physical condition profile of rock-climbing athletes in Bogor Regency - Hardiyono, Bayu; Nurkadri, Nurkadri; Pratama, Budiman Agung; Laksana, Anak Agung Ngurah Putra; Kurniawan, Febi (Universitas Nusantara PGRI Kediri, 2020)
This study aims to determine the physical condition of rock-climbing athletes in Bogor Regency. Besides, it is also to make the basis for providing training proportions and finding the right solution to overcome the physical condition problems of rock-climbing athletes in Bogor Regency. This study uses a descriptive method approach using tests and measurements. The sample in this study were 15 rock climbing athletes in Bogor Regency. The instrument used in retrieving the data is a test instrument that has been arranged in the test and manual measurement and is following the physical conditions used in the sport of rock climbing. The results showed that athletes in the very good category was 13.34%, then in the good category was 13.34%, then in the moderate category was 66.66%, also in the poor category was 6.66%, and then 0.00% in the poor category. Furthermore, for researchers who will develop this research they ought to cover a wider range of materials, because this research is limited to athletes in Bogor Regency only.